Newly Described Entities in Salivary Gland Pathology. (August 2017) - Skálová, Alena; Gnepp, Douglas R.; Lewis, James S.; Hunt, Jennifer L.; Bishop, Justin A.; Hellquist, Henrik; Rinaldo, Alessandra; Vander Poorten, Vincent; Ferlito, Alfio
Abstract : Salivary glands may give rise to a wide spectrum of different tumors. This review concentrates on 4 salivary gland tumors that have been accepted in the recent literature as new neoplastic entities: mammary analog secretory carcinoma, cribriform adenocarcinoma of minor salivary glands (CASG), sclerosing polycystic adenosis/adenoma (SPA), and the mucinous/secretory variant of myoepithelioma. Mammary analog secretory carcinoma is a distinctive low-grade malignant salivary cancer that harbors a characteristic chromosomal translocation, t(12;15) (p13;q25), resulting in an ETV6-NTRK3 fusion. Cribriform adenocarcinoma (CASG) is a distinct tumor entity that differs from polymorphous low-grade adenocarcinoma by location (ie, most often arising on the tongue), by prominent nuclear clearing, differing alterations of the PRKD gene family, and clinical behavior with frequent metastases at the time of presentation of the primary tumor. Early nodal metastatic disease is seen in most cases of CASG; yet, they are still associated with indolent clinical behavior, making it a unique neoplasm among all low-grade salivary gland tumors. SPA is a rare sclerosing tumor of the salivary glands characterized by the combination of cystic ductal structures with variable cell lining including vacuolated, apocrine, mucinous, squamous, and foamy cells, by prominent large acinar cells with coarse eosinophilic cytoplasmic zymogen-like granules, and by closely packed ductal structures, surrounded by a peripheral myoepithelial layer and stromal fibrosis with focal inflammatory infiltrates. SPA frequently harbors intraductal epithelial dysplastic proliferations ranging from mild dysplasia to severe dysplasia/carcinoma in situ. Moreover, SPA has been proven to be a clonal process by HUMARA assay and is associated with considerable risk of recurrence. Therefore, on the basis of all these newly recognized findings, we believe that SPA is likely a neoplasm, and we suggest the name "sclerosing polycystic adenoma." The mucinous variant of myoepithelioma is a myoepithelial tumor with foci of prominent cytoplasmic clearing frequently containing intracellular mucin material and having signet-ring morphology.